Security at sea : can anything be done at the Somali Coast? - Chan, Jane (2009)
Three months since it was put to a vote, it was obvious that the United Nations Resolution 1816 (2008) did not work as intended. Warships are now clearly present in Somali waters, yet they are not much of a deterrence to the number of hijacking incidences.